Genetic Diversity and Population Differentiation of Chinese Lizard Gudgeon (Saurogobio dabryi) in the Upper Yangtze River - Liu, Hongyan; Xiong, Fei; Zhai, Dongdong; Duan, Xinbin; Chen, Daqing; Chen, Yuanyuan; Wang, Ying; Xia, Ming (Frontiers in Ecology and Evolution, 2022)
Dam construction on the upper Yangtze River has dramatically altered riverine ecosystems and caused habitat fragmentation of fishes, which might influence genetic structure of fish populations. In this study, we examined the possible genetic effects of dam construction on Chinese lizard gudgeon (Saurogobio dabryi) populations in the upper Yangtze River, China. Seven populations were sampled and genetic structure was analyzed using SNP markers through the SLAF sequencing method. The numbers of SNPs were lower in the upstream populations than in the downstream populations. Genetic similarity increased from downstream to upstream. The upstream populations of S. dabryi might be more vulnerable to genetic drift than those downstream. Structure analysis indicated three distinct genetic groups of S. dabryi in the upper Yangtze River, among which the genetic differentiation values (Fst) were at a high level. The genetic differentiation of S. dabryi exhibited a close correlation with spatial distance. We did not detect significant correlation between isolation time and genetic differentiation, suggesting that impacts of dams on genetic structure of S. dabryi can be relatively minimal on a short time-scale. The results quantify the genetic diversity and population structure patterns of S. dabryi after habitat fragmentation caused by dams, which will provide a reference for resource protection and management of this species in the upper Yangtze River.